2019
DOI: 10.3389/fnins.2019.01009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Induced Sensory Nerve Growth and Pain Hypersensitivity Requires the N-Type Calcium Channel Cav2.2

Abstract: Voltage-gated calcium channels (VGCCs) are important mediators of pain hypersensitivity during inflammatory states, but their role in sensory nerve growth remains underexplored. Here, we assess the role of the N-type calcium channel Cav2.2 in the complete Freund’s adjuvant (CFA) model of inflammatory pain. We demonstrate with in situ hybridization and immunoblotting, an increase in Cav2.2 expression after hind paw CFA injection in sensory neurons that respond to thermal stimuli, but not in two different mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Briefly, slides were dehydrated in a graded series of alcohol, peroxidase activity was blocked with hydrogen peroxide, and protease IV was applied to the tissue for 30 minutes at room temperature before undergoing the RNAScope Multiplex Fluorescent v2 assay (ACD). The assay was performed according to the manufacturer's protocol using two probes as we have previously described 46 . TG sections were assessed for overlap between Tlr4 (channel 1) and either Trpa1, Trpv1, or Mrgprd (channel 2).…”
Section: Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, slides were dehydrated in a graded series of alcohol, peroxidase activity was blocked with hydrogen peroxide, and protease IV was applied to the tissue for 30 minutes at room temperature before undergoing the RNAScope Multiplex Fluorescent v2 assay (ACD). The assay was performed according to the manufacturer's protocol using two probes as we have previously described 46 . TG sections were assessed for overlap between Tlr4 (channel 1) and either Trpa1, Trpv1, or Mrgprd (channel 2).…”
Section: Scorementioning
confidence: 99%
“…However, our own preliminary studies and others 16 have shown that maxillary molar labeling with the DiI paste Neurotrace (Invitrogen) results in positive cells in all branches of the trigeminal nerve, therefore we imaged cell clusters observed in both the region where V3 and V2 meet, as well as the region where V1 and V2 meet, resulting in 2 images per section with the 20x objective. As we have previously described 46 all cells with detectable signal were selected for quantification and the signal intensity of mRNA clusters observed within each cell was analyzed by drawing a region of interest around each cell and mean signal intensity in arbitrary units generated by ImageJ software was noted. The dimensions of the region of interest were kept constant throughout the analysis to avoid bias.…”
Section: Scorementioning
confidence: 99%
“…Total protein of lysates was measured using standard BCA (Bicinchoninic Acid Assay). Protein lysates were then denatured by heating at 95 • C in Laemmli's buffer containing 2% w/v SDS, 62.5 mM Tris (pH 6.8), 10% glycerol, 50 mM DTT, and 0.01% w/v bromophenol blue (Pitake et al, 2019). The lysates were cooled on ice and briefly micro-centrifuged.…”
Section: Western Blotmentioning
confidence: 99%
“…It was shown that in the case of nifedipine, this is due to activation of TRPM3, TRPA1, and ionotropic glutamate receptors of the NMDA subtype [ 145 ]. A more novel approach might include antagonists of Ca v 2.2 [ 146 ]. Based on the caveats mentioned above, it is interesting whether a weak calcium-channel inhibitory component might contribute to the overall action of an analgesic drug.…”
Section: Effects Predominantly or Exclusively On Sensory Neuronsmentioning
confidence: 99%